Race Ends Where? Race, Racism and Contemporary Sociology. (December 2015) - Meer, Nasar; Nayak, Anoop
In this introductory article we critically discuss where the study of race in sociology has travelled, with the benefit of previously published articles in Sociology supported by correspondence from article authors. We make the argument for sociologies of race that go beyond surface level reconstructions, and which challenge sociologists to reflect on how their discipline is presently configured. What the suite of papers in this collection shows is both the resilience of race as a construct for organising social relations and the slippery fashion in which ideas of race have shifted, transmuted and pluralised. It is in a spirit of recognising continuity and change that we present this collection. Some of the papers already stand as landmark essays, while others exemplify key moments in the broader teleology of race studies. This includes articles that explore the ontological ground upon which ideas of race, citizenship and black identity have been fostered and the need to develop a global sociology that is critically reflexive of its western orientation. The theme of continuity and change can be seen in papers that showcase intersectional approaches to race, where gender, nationality, generation and class offer nuanced readings of everyday life, alongside the persistence of institutional forms of discrimination. As this work demonstrates, middle-class forms of whiteness often go 'hiding in the light' yet can be made visible if we consider how parental school choice, or selecting where to live are also recognised as racially informed decisions. The range and complexity of these debates not only reflect the vitality of race in the contemporary period but lead us to ask not so much if race ends here, but where?